The Role of Leadership Style on Employee Achievement - Rahayu, Puspita Puji (Program Pascasarjana STIE Amkop Makassar, 2023)
The Influence of Organizational Culture on Employee Achievement; and (2) The Influence of Leadership Style on Employee Achievement are the two main empirical research topics in this study. This study is quantitative in nature, collecting data through the use of questionnaires to get primary data. The 128 employees of the Human Resources Development Agency of the Central Java Province comprised the study's population. There are sixty-two employees' samples to be examined. In this study, questionnaires, documents, and observation were the methods employed for gathering data. Primary and secondary data sources yield both quantitative and qualitative data kinds. The tests for normalcy, heteroscedasticity, and multicollinearity are used in the classical assumption test. Keywoard: Organizational culture, leadership style, staff performance